Implementasi Model Pembelajaran Talking Stick Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IV SDN 1 Sedarat - Boyati; Reza Kusuma Setyansah; Octarina Hidayatus Sholikhah; Vera Octavianingrum (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This study aims to explain the application of the Talking Stick learning model to improve mathematics learning outcomes in polygonal shape material for fourth grade students at SD Negeri 1 Sedarat, Kec. Balong, Kab. Ponorogo. The problems that are often encountered in learning activities where the low enthusiasm of students in participating in learning is due to the learning process that is packaged by teachers who are less innovative and varied, so this is the background for researchers to design learning models that can solve these problems. The talking stick learning model which is more game-based is expected to be able to attract the enthusiasm of students in participating in classroom learning activities and also provide space for students at SDN 1 Sedarat to be more active, and willing to work together with others. The type of research conducted by researchers is the Kemmis & McTaggart Class Action Research model. The stages in this study were carried out in two cycles divided into 4 meetings. The subjects in this study were fourth grade students at SDN 1 Sedarat Kec. Balong, Ponorogo Regency, totaling 17 children. The increase in student learning outcomes in mathematics learning polygonal shape material with the talking stick model can be seen from the percentage of learning completeness in cycle I of 58.82%, while the percentage of completeness of learning outcomes in cycle II rises to 88.23%. Keywords: Talking Stick; Learning Outcomes; Mathematics.